2005
DOI: 10.2298/fupct0502183j
|View full text |Cite
|
Sign up to set email alerts
|

A study of the initial stages of the electrochemical deposition of metals on foreign substrates: Lead and thallium on copper and silver surfaces: General discussion

Abstract: Abstract. The basic applicability of the UPD theory of Gerischer et al. has been confirmed in the case of lead and thallium deposition on copper and silver single crystals, but it was shown also that this is only

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 74 publications
1
5
0
Order By: Relevance
“…7 and 8 indicate that the process of underpotential deposition of Ag on Rh(1 1 1) is more affected by silver concentration in perchloric acid than in sulfuric acid. The effect of changing the bulk concentration of the depositing material (that we confirm here) was also noticed before [24]. This effect was attributed to the change in electronegativity of the substrate and underpotential layer as a result of changing the electrode potential.…”
Section: Underpotential Deposition Of Ag On Rh Single Crystal Electrodessupporting
confidence: 83%
See 1 more Smart Citation
“…7 and 8 indicate that the process of underpotential deposition of Ag on Rh(1 1 1) is more affected by silver concentration in perchloric acid than in sulfuric acid. The effect of changing the bulk concentration of the depositing material (that we confirm here) was also noticed before [24]. This effect was attributed to the change in electronegativity of the substrate and underpotential layer as a result of changing the electrode potential.…”
Section: Underpotential Deposition Of Ag On Rh Single Crystal Electrodessupporting
confidence: 83%
“…Cyclic voltammetry was broadly employed to investigate the difference between peak potential of the UPD monolayer formation and that of the bulk deposition [16,[22][23][24], that is, the UPD shift. Kolb et al [22] showed that such a UPD shift was related to the difference between the work function of substrate and deposit.…”
Section: Introductionmentioning
confidence: 99%
“…(30) into Eqs. (28) and (29), multiplying the results by √ 2Aτ and rearranging the obtained equation, one has: Fig. 13.…”
Section: Diffusion With the Formation Of 2 Intermediate Compoundsmentioning
confidence: 99%
“…In solutions, it has been a subject of research for more than fifty years [23][24][25][26][27][28][29][30]. Soon, the phenomenon of UPD from melts [12,20,31,32] was also recognized, and it was well documented in the case of aluminium UPD from inorganic [12,14,33,34] and organic melts (ionic liquids) [7,12,[35][36][37].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation